Development of Disaster Management Information System Application with Five Integrated Features - Samhuri, Refita Yunie; Yonvitner, Yonvitner; Arkeman, Yandra (Information Technology and Science (ITScience), 2025)
Indonesia, as one of the world’s largest archipelagic countries, is highly prone to natural disasters due to its geological, geographical, and socio-demographic conditions. Despite various efforts from the government and related institutions, there remains a lack of an integrated technological solution that addresses the critical aspects of disaster management. This research aims to develop a mobile-based disaster management information system called Aksi Bencana Indonesia, featuring five integrated functions: real-time disaster information, donation facilitation, volunteer management, logistics coordination, and disaster education. The development process involved identifying functional and non-functional requirements through interviews with disaster mitigation experts and literature studies, followed by UI/UX design using Figma, and coding using Flutter for the frontend and Laravel for the backend. User Acceptance Testing (UAT) was conducted with participants aged 18–55 to evaluate the system’s usability and effectiveness. The results showed that the application met the users’ expectations in providing timely and reliable information, facilitating donations and volunteer coordination, and supporting educational initiatives. Moreover, the integration of real-time features improved response time and enhanced the efficiency of resource distribution during disaster events. This study concludes that the application successfully bridges the gap between communities, donors, and volunteers, offering a practical solution for disaster preparedness and response. Future research may focus on expanding the system’s interoperability with national disaster databases and enhancing the analytics dashboard for better decision-making.